Further insights into the anti-PF4/heparin IgM immune response - Krauel, Krystin; Schulze, Annika; Jouni, Rabie; Hackbarth, Christine; Hietkamp, Bernhard; Selleng, Sixten; Koster, Andreas; Jensch, Inga; Linde, Julia van der; Schwertz, Hansjörg; Bakchoul, Tamam; Hundt, Matthias; Greinacher, Andreas (Thrombosis and Haemostasis, 2016)
Anti-platelet factor 4 (PF4)/heparin antibodies are not only the cause of heparin-induced thrombocytopenia but might also play a role in the antibacterial host defence. Recently, marginal zone (MZ) B cells were identified to be crucial for anti-PF4/heparin IgG antibody production in mice. Combining human studies and a murine model of polymicrobial sepsis we further characterised the far less investigated anti-PF4/heparin IgM immune response. We detected anti-PF4/heparin IgM antibodies in the sera of paediatric patients < 6 months of age after cardiac surgery and in sera of splenectomised mice subjected to polymicrobial sepsis. In addition, PF4/heparin-specific IgM B cells were not only found in murine spleen, but also in peritoneum and bone marrow upon in vitro stimulation. Together, this indicates involvement of additional B cell populations, as MZ B cells are not fully developed in humans until the second year of life and are restricted to the spleen in mice. Moreover, PF4/heparin-specific B cells were detected in human cord blood upon in vitro stimulation and PF4-/- mice produced anti-PF4/heparin IgM antibodies after polymicrobial sepsis. In conclusion, the anti-PF4/heparin IgM response is a potential innate immune reaction driven by a B cell population distinct from MZ B cells.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: HIT; anti-PF4/heparin antibodies; B cells; immune response